PERFORMANCE ANALYSIS OF SMALL AND MEDIUM ENTERPRISES IN THAILAND - Kongkadvanich, Lamida; Sincharoonsak, Titaporn (Journal of MCU Nakhondhat, 2020)
This article aims to study general information on small and medium enterprises in Thailand and to analyze the performance of small and medium enterprises in Thailand. It uses the quantitative analysis to analyze the performance of small and medium enterprises. This study used 260 samples. The research instrument were questionnaires. The questions have confidence by validity and reliability were examined with the Cronbach's Alpha coefficient having α greater than 0.7. The descriptive statistics in the study were mean, percentage and standard deviation. The research was found that most of the sample groups had a registered capital of more than 5 million baht, but not over than 10 million baht, operated their business more than 15 years but not over than 20 years, and had fewer or 50 employees, and the rate of return on assets (ROA) was mostly equal to 0.21 - 0.40 while the profit margin ratio (Net Profit Margin) is mostly 6% - 10% and the Capacity Utilization rate is 68% - 75%. Make them aware of the ability to use assets to generate income. Financial performance can be measured by operating income or cash flow from operations or total sales. An analyst or investor may want to monitor deeper into finance. Analysts and investors may look deeper at financial statements and growth rates as performance indicators of small and medium enterprises in Thailand.